Synthesis of Copper Telluride Thin Films by Electrodeposition and Their Electrical and Thermoelectric Properties - Park, Jungjoon; Seo, Jinmyeong; Lim, Jae-Hong; Yoo, Bongyoung (Frontiers in Chemistry, 2022)
Intermetallic copper telluride thin films, which are important in a number of electronics fields, were electrodeposited using a potentiostatic method in low-pH aqueous electrolyte baths with various ion-source concentrations, and the electrical properties of the formed films were investigated after exfoliation from the substrate. The films were electrochemically analyzed by cyclic voltammetry, while surface and cross-sectional morphologies, compositional ratios, and electrical properties were analyzed by scanning electron microscopy, X-ray diffractometry, X-ray photoelectron spectroscopy, ultraviolet photoelectron spectroscopy, and Hall-effect experiments. The copper telluride thin films, which were synthesized at various potentials in each bath, exhibit different composition ratios and structures; consequently, they show a variety of electrical and thermoelectric properties, including different electrical conductivities, carrier concentrations, mobilities, and Seebeck coefficients. Among them, the thin film with a 1:1 Cu:Te ratio delivered the highest power factor due to carrier filtering at the interface between the two phases.